Glass transition of polystyrene (PS) studied by Raman spectroscopic investigation of its phenyl functional groups. (16th January 2017) - Menezes, D Bertoldo; Reyer, A; Marletta, A; Musso, M
Abstract: In polymeric materials the glass transition (GT) is a well-known and very important relaxation process related to movements of functional groups in the polymeric chain. In this work, we show the potential of Raman spectroscopy for exploring the GT process in the polymer polystyrene. We collected Raman spectra during a step-by-step heating process of the sample, which allowed us to collect signatures of the GT process from peak parameters of specific vibrational modes, and to verify the GT temperature. Results of the latter were in accordance with published values obtained via other methods. We identified the aromatic ring vibrational modes of the phenyl functional groups to be those which, due to steric hindrance, suffer the largest influence during the GT process. This confirms that Raman spectroscopy can be used as a complementary technique to perform GT investigations in polymeric materials due to its sensitivity to small intermolecular changes affecting vibrational properties of relevant functional side groups.